2015
DOI: 10.1007/s00784-015-1551-z
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and serum interleukin-6 levels in proliferative verrucous leukoplakia

Abstract: Salivary and plasma IL-6 are altered in patients with PVL, with more extensive verrucous areas being associated to the highest IL-6 levels. This could be a significant tool for monitoring patients with PVL, their progression to more advances stages and their recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
1
18
0
3
Order By: Relevance
“…Fourteen studies included controls and compared their results with either normal oral mucosa, conventional oral leukoplakia, reactive lesions, or malignant tumors . Ten studies only analyzed biomarker expression (whether the biomarkers were present or not/strength of staining) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies included controls and compared their results with either normal oral mucosa, conventional oral leukoplakia, reactive lesions, or malignant tumors . Ten studies only analyzed biomarker expression (whether the biomarkers were present or not/strength of staining) .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies only analyzed biomarker expression (whether the biomarkers were present or not/strength of staining) . Four studies analyzed how biomarker expression was association with clinical and/or histological data . Three studies correlated the biomarkers expression with progression and/or malignant transformation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated valuable associations among OSCC clinical stages and prognosis, and salivary or serum markers associated with TAM’s dynamic participation in the tumour stroma [58, 68, 7073]. Although salivary markers associated to TAM polarization are not yet used as parameters for definitive diagnoses, they should be taken into consideration to evaluate patients with potent malignant disorders, like proliferative verrucous leukoplakia [74], as well as for recurrence in OSCC treated patients.…”
Section: Introductionmentioning
confidence: 99%